The ischemia modified albumin and mean platelet volume levels in patients with Behçet’s disease - Kılıç, Sevilay; Işık, Selda; Hiz, Meliha Merve; Çakır, Dilek Ülker; Türkön, Hakan; Cevizci, Sibel; Ogretmen, Zerrin (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Behçet’s disease (BD) is a chronic inflammatory disorder with endothelial dysfunction. Ischemia-modified albumin (IMA) is a marker used in the detection of diseases associated with oxidative stress, vascular endothelial cell dysfunction and ischemia. Mean platelet volume (MPV) signifies the platelet function and activity. Aim: To show whether MPV and IMA are useful in revealing the oxidative stress and the risk of thrombosis in patients with BD. Material and methods : Twenty-six patients with BD and 28 healthy volunteers as a control group over 18 years of age were included in the study. Serum IMA and MPV levels were analyzed in both groups. Results: The mean MPV values were identified as 0.86 ±0.15 and 0.82 ±0.08 (in the BD and control groups, respectively; p = 0.188) and the mean IMA values were 9.39 ±0.73 and 9.17 ±1.09 (in the BD and control groups, respectively; p = 0.275). There were no statistically significant differences between the groups. The IMA values of BD patients who were in the active phase were significant as compared to inactive BD patients and control groups (p = 0.041). The IMA and MPV values of the thrombotic patients, non-thrombotic patients and control groups were not significant. Conclusions : Ischemia-modified albumin may be a helpful marker of possible complications during an active period of BD.